Congenital Absence of the Anterior Cruciate Ligament in Monozygotic Twins - Sonn, K. A.; Caltoum, C. B. (International Journal of Sports Medicine, 2014)
Cases of congenital absence of the cruciate ligaments are seen rarely in the literature. When reported, they are almost exclusively associated with various additional lower extremity deformities. We report the cases of 15-year-old monozygotic twin brothers. Both brothers presented with right knee pain and instability and were found on magnetic resonance imaging (MRI) to have congenital absence of the right anterior cruciate ligament (ACL). Examination of full length leg radiographs and MRI of the knee showed no associated abnormalities. Twin B previously underwent partial medial meniscectomy performed by an outside orthopaedic surgeon at which time the absence of the ACL was noted but not repaired. After diagnosis at our practice, both twins underwent arthroscopically assisted ACL construction with bone-patella-bone-autograft. Following recovery from surgery, both twins returned to high level athletics. These cases are among few reports of isolated congenital absence of the ACL, and to our knowledge there are no other cases of isolated congenital absence of the ACL in monozygotic twins.
Keywords: ACL; deficiency; reconstruction